Volume information in Nikkei and TOPIX futures transactions - TEE, Chyng Wen (Institutional Knowledge at Singapore Management University, 2017)
According to the Kyle (1985) model of informed trading, information in trade size is likely to effect a permanent price impact. However, two prominent structural models in the literature do not include trade size in their framework. In this paper, we present a nesting relationship of major structural models and formulate a generalized model that includes all trade variables. A new measure to quantify the amount of information in the order flow is proposed. Our empirical analysis shows that it is indeed the "surprise" in trade size that contributes significantly in reflecting the price change of Nikkei and TOPIX futures.